Ethical Awareness of Educators Toward AI Usage: A Study on Bias, Privacy, and Responsible Implementation - Wardani Wardani; Mutia Velli Agusta (CV. FoundAE, 2025)
The increasing use of artificial intelligence in education has intensified concerns regarding algorithmic bias, data privacy, and the ethical responsibilities of educators, yet little is known about how educators understand and respond to these ethical challenges. This quantitative study examined the extent to which educators’ awareness of bias and privacy predicts their commitment to responsible AI implementation. A total of 214 educators participated in a cross-sectional survey that included validated measures of bias awareness, privacy awareness, and responsible implementation. Data were collected online and analyzed using descriptive statistics, correlations, and multiple regression. Results showed that both bias awareness and privacy awareness were significant predictors of responsible AI use, with the model explaining 46% of the variance. Educators reported moderate to high awareness across ethical domains, and effect sizes indicated meaningful relationships among variables. These findings highlight the central role of ethical literacy in shaping how educators adopt and regulate AI tools in classroom contexts. The study contributes a data-driven understanding of ethical awareness in AI-mediated education and underscores the need for professional development and policy frameworks that equip educators to navigate emerging ethical challenges.